Mechanized instrumentation in endodontic treatment of primary teeth: An integrative review (Research, Society and Development, 2023)
The health of baby teeth is crucial for children's quality of life, but caries is common and can lead to complex treatments. Problems such as the collaboration of children and the complexity of root canals make treatment difficult. Thus, mechanical instrumentation is preferred to manual files, as it cleans the channels better, speeds up the treatment and creates more uniform and predictable channels. This study aims to review the advantages and disadvantages of the use of mechanized instrumentation in the treatment of deciduous teeth, based on scientific articles from reputable sources such as SciELO, MEDLINE, PubMed, Springer and Periódicos Capes. After a survey that initially found 575 articles, 12 of them were selected for the study based on inclusion and exclusion criteria. These articles were published between 2018 and 2022, with 2019 having the highest number of publications (5), followed by 2022 (4) and 2018 (2). A 2020 study was also included, but no 2021 studies were selected, due to a lack of publications this year. The use of mechanized instrumentation to treat baby teeth is showing promise, offering greater efficacy, safety and accuracy compared to traditional manual methods. However, there is a lack of clinical studies in this area, highlighting the need to conduct more research.